Environmental legacy of pre-Columbian Maya mercury - Cook, Duncan E.; Beach, Timothy P.; Luzzadder-Beach, Sheryl; Dunning, Nicholas P.; Turner, Simon D. (Frontiers in Environmental Science, 2022)
The Mexico and Central American region has a history of mercury use that began at least two millennia before European colonisation in the 16th century. Archaeologists have reported extensive deposits of cinnabar (HgS) and other mercury materials in ancient human settlements across the region. However, there has been no consideration to date of the environmental legacy of this long history of anthropogenic mercury use. This review begins by synthesising our knowledge of the history and nature of anthropogenic mercury in ancient Mesoamerica based on archaeological data, with a particular focus on the Maya culture of lowland Guatemala, Belize, the Yucatan of Mexico, El Salvador, and Honduras. The Classic Period Maya used mercury for decorative and ceremonial (including funerary) purposes: Cinnabar (HgS) predominantly, but the archaeological record also shows rare finds of elemental mercury (Hg0) in important burial and religious contexts. In this review, we have located and summarised all published data sets collected from (or near) ancient Maya settlements that include environmental mercury measurements. Comparing mercury determinations from Pre-Columbian Maya settlements located across the region confirms that seven sites from ten have reported at least one location with mercury concentrations that equal or exceed modern benchmarks for environmental toxicity. The locations with elevated mercury are typically former Maya occupation areas used in the Late Classic Period, situated within large urban settlements abandoned by c. 10th century CE. It is most likely that the mercury detected in buried contexts at Maya archaeological sites is associated with pre-Columbian mercury use, especially of cinnabar. In more complex contexts, where modern biological or specifically anthropogenic inputs are more probable, legacy mercury in the environment will have a more complex, and time transgressive input history. This review identifies current research gaps in our understanding of the long history of Maya mercury use and in the collection of robust total mercury datasets from the Maya world. We identify important areas for future research on the environmental persistence and legacy of mercury, including the need to interpret environment mercury data in the context of mercury exposure and human health at Maya archaeological sites.